A New Historical Approach to John Donne’s A Valediction: Forbidding Mourning - Pooyan Changizi; Parvin Ghasemi (K@ta: A Biannual Publication on the Study of Language and Literature, 2010)
A Valediction: Forbidding Mourning is one of John Donne’s most celebrated and most significant poems in which he declares, quite ingeniously, his ideal of spiritual love which transcends the ordinary and inferior love of others that is based on mere physicality. This essay applies New Historicism, a school of literary theory since the early 1980s, to Donne’s seventeenth-century poem. The study begins with elaborating on the major concepts and principles of New Historicism. Then, the historical, cultural and biographical circumstances that surrounded and motivated the composition of Donne’s poem are discussed. Finally, the discourses of religion, science, love, sexuality, space and time and the circulation of power implicit in the compass imagery, the metaphysical conceit used in this poem, are explored.